Oyster (Crassostrea gigas) Hydrolysates Produced on a Plant Scale Have Antitumor Activity and Immunostimulating Effects in BALB/c Mice - Yu-Kai Wang; Hai-Lun He; Guo-Fan Wang; Hao Wu; Bai-Cheng Zhou; Xiu-Lan Chen; Yu-Zhong Zhang (Marine Drugs, 2010)
Oyster extracts have been reported to have many bioactive peptides. But the function of oyster peptides produced by proteolysis is still unknown. In this study, the oligopeptide-enriched hydrolysates from oyster (Crassostrea gigas) were produced using the protease from Bacillus sp. SM98011 at laboratory level, and scaled up to pilot (100 L) and plant (1,000 L) levels with the same conditions. And the antitumor activity and immunostimulating effects of the oyster hydrolysates in BALB/c mice were investigated. The growth of transplantable sarcoma-S180 was obviously inhibited in a dose-dependent manner in BALB/c mice given the oyster hydrolysates. Mice receiving 0.25, 0.5 and 1 mg/g of body weight by oral gavage had 6.8%, 30.6% and 48% less tumor growth, respectively. Concurrently, the weight coefficients of the thymus and the spleen, the activity of natural killer (NK) cells, the spleen proliferation of lymphocytes and the phagocytic rate of macrophages in S180-bearing mice significantly increased after administration of the oyster hydrolysates. These results demonstrated that oyster hydrolysates produced strong immunostimulating effects in mice, which might result in its antitumor activity. The antitumor and immunostimulating effects of oyster hydrolysates prepared in this study reveal its potential for tumor therapy and as a dietary supplement with immunostimulatory activity.